Leveraging ChatGPT for Personalized Learning: A systematic Review in Educational Settings - A.H Sahna Sreen; M.H.M. Majid (Amandemen: Journal of Learning, Teaching and Educational Studies, 2024)
In today’s digital world, personalization is a leading point for each learner to strengthen their educational achievements. Considering innovations in artificial intelligence (AI), particularly in the area of natural language processing, Chat GPT has sparked awareness as a viable mechanism for supporting personalized learning. The aim of the systematic review is to identify the present-day status of research on using Chat GPT for independent learning in educational settings. The research effort combines works that study Chat GPT application in learning environments, summarizing the results of a broad survey of scholarly literature. The significance of the Chat GPT in the learning path was identified from the previous studies. Also, the study discusses the practical difficulties and challenges of this technology. The study highlights some potential improvements by the Chat GPT, like improving the individual learning experience, offering seamless feedback and error corrections, encouraging study, and finding study metrics. Also, the study identified some potential challenges, for example, data privacy, bias, accessibility of databases, and similarity between answers. There is a possibility for further research on this topic in advance to get more valuable ideas in the academic field. This comprehensive study examines a collection of AI-based personalized learning ideas to clearly enlighten the advantages and disadvantages of utilizing Chat GPT in an academic environment. Practitioners can gain a clear idea by referring to the article, which will maximize the usage of technology in the near future.